Producing Stainless Steel (SS16L) with Hydroxyapatite (HA) via Slurry Method - R . Yarshine Rani; Ahmad, sufizar; F . Mat Noor (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Stainless steel is now widely used metal in biomedical applications such as implants, which are used to replace structural features of the human body. The bioactive and biological advantage of hydroxyapatite (HA) for the bony tissue impact is to be established as the material of choice for implant applications. The slurry process was used to fabricate stainless steel-hydroxyapatite foam with various Hydroxyapatite powder compositions of 1 wt%, 3 wt %, 5 wt %, 7 wt% , and 10 wt %. Binders such as Polyethylene Glycol (PEG), Carboxymethyl Cellulose (CMC), and distilled water were used. Raw materials was stirred using a mechanical stirrer, and polyurethane (Pu) cylinders with dimensions of 22-24mm length and 15-16mm diameter was submerged in SS316L-HA slurry until completely coated. The coated material was dried inside a drying oven at 40 ° C for 24 hours before being sintered at 1200 ° C in tube furnace containing argon gas. A mechanical stirrer was used to mix the raw materials, and polyurethane (Pu) cylinders measuring 22-24mm in length and 15-16mm in diameter were immersed in the SS316L-HA slurry until fully coated. The coated material were dried for 24 hours at 40 ° C inside a drying oven before even being sintered at 1200 ° C in an argon-gas-filled tube furnace. The result of density are in range of 0.857g/cm³-2.335g/cm³ and porosity in range of 56.20%-84.39%. SS316L-HA were successfully developed by using slurry method.